2020
DOI: 10.18805/ijare.a-5485
|View full text |Cite
|
Sign up to set email alerts
|

Resource Use Efficiency, Productivity and Profitability of Bt Cotton (interspecific) as Influenced by Crop Geometry and Drip Fertigation

Abstract: Background: Cotton is one of the important commercial crops cultivated in India for fibre and oil. The average cotton productivity of India is lower compared to other countries. Among the improved agronomic practices, important yield contributing agro techniques are crop geometry and fertilizer application. Drip irrigation and use of water soluble fertilizers (WSF) by drip system is a recommended practice to increase both water and nutrient use efficiency. Taking this aspect, a field investigation was carried … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
1
0
0
Order By: Relevance
“…India's cotton production has increased tremendously during the past 22 years due to the introduction and rapid geographical expansion of bollworm resistant Bt cotton. It is a practical management strategy for growing interspecific Bt cotton that produces good yields (Baskar and Jagannathan, 2021). The pertinent arguments presented in this article support the analytical discussion of the cotton trade's yearly trends.…”
supporting
confidence: 52%
“…India's cotton production has increased tremendously during the past 22 years due to the introduction and rapid geographical expansion of bollworm resistant Bt cotton. It is a practical management strategy for growing interspecific Bt cotton that produces good yields (Baskar and Jagannathan, 2021). The pertinent arguments presented in this article support the analytical discussion of the cotton trade's yearly trends.…”
supporting
confidence: 52%
“…Similar results were obtained by Ansari and Rana (2012) and Singh et al (2019). Baskar and Jagannathan, 2021 reported that all the yield attributing characters were higher under the wider spacing (120  60) in cotton. Intercropping system did not influence the earhead length and width of pearlmillet.…”
Section: Price Of Pearlmilletmentioning
confidence: 99%